2021
DOI: 10.3390/ijerph19010309
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Return to Work and Mortality in Lung Cancer Survivors

Abstract: Lung cancer is the second most common cancer and the leading cause of cancer-related deaths worldwide. Return to work (RTW) plays an important role for lung cancer survivors. Few studies focus solely on the relationship among possible variables and the RTW of lung cancer patients. The aim of our study was to examine sociodemographic, disease-related and work-related factors associated with RTW among lung cancer survivors in Taiwan. A total of 2206 employees who had been diagnosed with lung cancer at the Labor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…This study also reported that patients who returned to work had a significantly reduced risk of all-cause mortality with a hazard ratio of 0.46 (95%-CI: 0.44–0.48), after controlling for age, treatment, income range, industrial classification, company size, and cancer stage. Other results confirmed that a better survival rate was seen in patients with stage III and IV lung cancer who returned to work [ 14 ]. In line with these findings, a systematic review revealed that lung cancer survivors in employment had a better quality of life regarding their physical functioning [ 13 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This study also reported that patients who returned to work had a significantly reduced risk of all-cause mortality with a hazard ratio of 0.46 (95%-CI: 0.44–0.48), after controlling for age, treatment, income range, industrial classification, company size, and cancer stage. Other results confirmed that a better survival rate was seen in patients with stage III and IV lung cancer who returned to work [ 14 ]. In line with these findings, a systematic review revealed that lung cancer survivors in employment had a better quality of life regarding their physical functioning [ 13 ].…”
Section: Discussionmentioning
confidence: 56%
“…Work plays an important role in lung cancer survival [ 13 ]. A better survival rate was found in stage III and IV lung cancer patients who had returned to work [ 14 ]. However, the return to work among cancer survivors is not always possible due to sociodemographic, work-related, and clinical-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the heterogenous nature of the studies, including control groups used, precluded a quantitative analysis of the return to work-rate of lung cancer survivors [ 7 ]. On the other hand, registry studies in patient populations originating in societies characterized by free healthcare and social security programs much like Denmark, have found return to work rates for lung cancer patients in general to be between 33 and 45% [ 10 , 33 , 34 ]. Among these, Rashid et al [ 10 ] found that 33% of working age (<65 years of age) German lung cancer survivors were affiliated with the labor market about one year following diagnosis, with the mean time to return to work being 13 months [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presenting the duration of the employee's treatment for cancer 66 ( mortality in lung cancer survivors reported higher survival rates for patients with stage III and IV lung cancer who returned to work. 10 Return of employees with cancer to the workplace is an important contributor to cancer patient survival rate, mental health, and QOL. The most common support provided by business establishments for employees with cancer was "Sickness and injury benefits" (49.7%), followed by "Paid leave on an hourly basis" (42.5%), and "Shorter working hours" (26.8%).…”
Section: Content To Be Performed With the Permission Of The Individualmentioning
confidence: 99%
“…8 It has been reported that returning to the workplace by patients with cancer who had previously worked improves their mental health and prognosis. 9,10 For employees with cancer to balance work and treatment, support from employers and coworkers and their understanding of cancer and its treatments are important.…”
mentioning
confidence: 99%